Consumers' segmentation based on the acceptability of meat from entire male pigs with different boar taint levels in four European countries: France, Italy, Spain and United Kingdom. (April 2016) - Panella-Riera, N.; Blanch, M.; Kallas, Z.; Chevillon, P.; Garavaldi, A.; Gil, M.; Gil, J.M.; Font-i-Furnols, M.; Oliver, M.A.
Abstract: Two consumer studies were conducted to know the acceptability of pork with different boar taint levels: test 1 performed in Spain (n = 126) and United Kingdom (n = 146), and test 2 performed in France (n = 139) and Italy (n = 140). Each test had 3 types of pork: 'Female meat', 'Low boar tainted meat', and a third type was 'Medium boar tainted meat' or 'High boar tainted meat'. Three main clusters were identified on the basis of 'How delicious do you find this meat?': 1—Pork lovers, 2—Boar meat lovers, 3—Reject boar tainted meat. Additionally, in test 2, a fourth cluster was identified: 'Reject low tainted meat'. A group of 16.2–38.2% of consumers rejected meat from boars, and another group of 12.4–21.7% rated the meat with medium or high levels of boar taint better than the meat from females, identifying a niche for meat from medium and high levels of boar taint, and suggesting the need to select carcasses on the basis of boar taint. Highlights: Consumer acceptability of entire male pork at eating A segment of pork lovers, regardless of the level of boar taint, has been identified. A segment of boar meat lovers and another that rejects boar tainted meat was found. There is a niche for meat from medium and high levels of boar taint. Meat classification according to boar taint level is needed to better orientate it.